STUDY OF DIESEL POWER PLANT REPLACEMENT WITH AN OFF-GRID SOLAR PHOTOVOLTAIC SYSTEM - Gustiyadi Fathur Rahmandi; Atok Setiyawan; Hendro Nurhadi (JIPOWER : Journal of Intellectual Power, 2025)
The electrification ratio on the island of Kalimantan has increased significantly from 2014 to 2024, significantly impacting people's lives, especially in Central Kalimantan Province. North Barito Regency is one of the regions that continues to strive to meet the electricity needs of its residents who still lack access to electricity, especially in the 3T (Outermost, Frontier, and Disadvantaged) areas through the Electrification Ratio (RE) program. This vast area presents a unique challenge in ensuring the equitable distribution of electricity to these 3T areas. To meet the National RE target and utilize the various types of power plants currently available in North Barito Regency, as well as to support the transition to New and Renewable Energy (EBT), PLN is connecting the existing electricity grid to the new grid through a network expansion scheme in urban areas. Meanwhile, in the 3T areas, renewable energy is being utilized, such as the construction of solar power plants (PLTS) capable of providing a 24-hour electricity supply. The main obstacles facing PLN (State Electricity Company) in Kalimantan in implementing this RE program include inadequate road access and road conditions for transporting electricity grid infrastructure materials, weather conditions (rain can slow work progress), and permits for 20 kV electricity grid infrastructure from individuals, groups, organizations, or business entities. This research will outline a plan to replace diesel-powered plants (PLTD) with off-grid solar power plants (PLTS) as a renewable energy source, taking into account operating load patterns and the efficiency of the solar power plants, based on the PV panel materials used: monocrystalline and polycrystalline. It is hoped that this study will provide information on the impact of PLTS development on the existing electricity system, enabling PLN to be more efficient in supporting the achievement of a 23% renewable energy mix by 2025.